Influence of methodology on the measurement of ileal endogenous calcium losses in broiler chickens. Issue 1 (1st January 2020) - Anwar, Muhammad Naveed; Ravindran, Velmurugu
ABSTRACT: An experiment was conducted to determine the ileal endogenous calcium (Ca) losses in four-week old male Ross 308 broiler chickens (mean body weight ± SD, 1.66 ± 0.12 kg) using three assay methodologies. Three experimental diets were used: a Ca and phosphorus (P)-free diet and two other diets by substituting (w/w) 200 g/kg dextrose (w/w) with maize gluten meal or dried egg albumen as Ca-free protein sources. Each of the three experimental diets was randomly allocated and fed for three days to six replicate cages (six birds/cage), and ileal digesta were collected to measure the ileal endogenous Ca losses. The feed intake of birds fed diets containing the two protein sources was higher ( P <  0.05) than the Ca and P-free diet. Body weight loss was observed in birds on the Ca and P-free diet and maize gluten meal-based diets. Ileal endogenous Ca losses were influenced ( P <  0.05) by the assay methodology. Ileal endogenous Ca losses were determined to be 125, 77 and 46 mg/kg dry matter intake in birds fed the Ca and P-free diet, maize gluten meal diet and dried egg albumen diet, respectively. Ileal endogenous P losses were determined in birds fed Ca and P-free and dried egg albumen based diets. There was no effect ( P >  0.05) of methodology on ileal endogenous P losses.